The Effect of Motor Balance Training on Certain Physical Variables and Skill Performance of Junior Futsal Players - Razaq Hussein Oudh, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
This study aims to highlight the importance of balance for futsal players, especially youth teams, during training programs, and its impact on certain physical variables and skill performance. It is based on important training theories and methods that should be applied in futsal, given the different nature of performance in futsal. In this game, the researcher used the experimental method with two equivalent groups (experimental and control) through pre- and post-testing, as it suited the nature and objectives of the research. The experimental factor was applied to a research sample consisting of (20) players, and the research sample of (16) players was determined. They were randomly divided into two equal groups: an experimental group of (8) players and (4) players were used for the pilot sample. The following results were obtained: that the exercises prepared according to the kinetic balance training had an effect on the development of physical and skill variables in the research sample. We recommend focusing on balance training to develop the physical variables and skill performance of futsal players. It is also essential to integrate balance training into training sessions alongside physical and skill-based training, and to conduct similar studies on different samples at other stages.